Native chiefs' observation as a new approach in solving the conflict of jurisdictions in the administration of justice: a case study of the native courts of Kota Kinabalu and Penampang, Sabah / Rafidah @ Malissa Salleh, Nur Asma Yahaya and Fazlin Mohamed Zain - Salleh, Rafidah @ Malissa; Yahaya, Nur Asma; Mohamed Zain, Fazlin (Faculty of Law, 2011)
Native law is administered by the Native courts established under the Sabah Native Courts Enactment 1992, which replaced the Native Courts Ordinance 1953. One of the problems faced by the courts is the conflict between the Native law and the Penal Code, in particular cases of rape and incest, where the choice is given to the victim, whether or not to have the rape or incest cases to be heard by the civil court or the Native court. This conflict of jurisdiction receives different responses from legal practitioners, the Native Chiefs and some of the NGOs. The Sabah Muslim Women Lawyers Association (Salwa) believes that Native Courts have no jurisdiction to hear cases involving rape and incest. The former Chairperson of the Sabah Women's Advisory Council (MPWS), Datuk Noni J. Said also endorsed Salwa's view. She also concurred with Assistant Minister of Community Development and Consumer Affairs, Jornah Mozihim who said punishment meted out by the Native Court is minimal and does not act as a deterrent. By simply using the buffalo to settle a rape case only allows potential perpetrators to take advantage of innocent village girls. This research aims to critically analyse the conflict of jurisdictions and other problems in the administration of the Native law and to make recommendation that would address legal problems in the administration of the Native Law. The research will be a qualitative research, where semi-structured interviews will be conducted with relevant respondents. It is expected that the outcomes of the research will contribute to the literature and enhance legal knowledge on the conflict of jurisdictions and other problems in the administration of Native law, and benefit the policy makers to review its existing laws into a more comprehensive framework in enhancing the administration of the Native law in Sabah.